Semantic changes in virus and pandemic from corpus linguistics and sociolinguistics - Brosa Rodríguez, Antoni (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
The coronavirus has promoted the semantic change in the words virus and pandemic. We believe that, increasingly, a metaphorical use of both words is occurring (as happened in the past with cancer). Therefore, in this study, the semantic characteristics of this change are systematized and detailed in the first place. Subsequently, we have designed a corpus with 480 sentences, balanced sociolinguistically to analyze the change quantitatively and qualitatively. Quantitatively, it will be reviewed if the change is present in all social groups and if any group promotes it. Qualitatively, it will be found that the metaphorical use of virus, pandemic and cancer is complementary: each of these words is used in very specific semantic collocations.